An Analysis of Subtitling Strategies of Indonesian Subtitles on The Movie Entitled “Harry Potter And The Sorcerer’s Stone” - Aurellia Ardia Pramatana (Jurnal Linguistik Terapan, 2021)
Harry Potter and The Sorcerer’s Stone is one of the successful movie adaptations from a famous novel by J.K Rowling which has been translated into 80 languages worldwide. Because of this success the research conducted focuses on analysis of the subtitles. The procedures to collect the data, the researcher used several steps: finding, observing, and analyzing. Finding the movie script as the material, observing the subtitling strategies that are used by translator in the movie and analyzing the strategies that are found in the subtitles. The methods used was descriptive analysis on Indonesian script as the material taken from extracted subtitles from the DVD and had been analyzed using Henrik Gottlieb theory. The aims of the research to analyze the subtitling strategies which applied in English- Indonesian subtitles in the “Harry Potter and The Sorcerer’s Stone” movie by the translator. The subtitling strategies that the researcher used are the one from Gottlieb’s theory, where they are expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, deletion, and resignation. This research used a descriptive qualitative approach to describe the results of the analysis of subtitling strategies, the object of this research is “Harry Potter and The Sorcerer’s Stone” movie subtitle. Percentage of the strategies that occurred in the English-Indonesian subtitles were transfer 72.8%, paraphrase 16.7%, imitation 0.29%, transcription 0.19%, decimation 0.18%, deletion 0.30% was found in Indonesian subtitle of “Harry Potter and The Sorcerer’s Stone” and transfer is one of the strategies which mostly applied by the translator.